The virtue of the justice like axis of the ethical reasoning of the communicator - Codina, Mónica (2022)
Communicator needs to develop a prudential knowledge. It feeds of the professional experience, but it not only has practical character. The ethical training grows when it is founded on criteria of rationality that philosophical ethics contributes. The present article considers how the virtue of the justice, according Aristotle, can orientate a public ethical communication.